If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4x + -5 + 3yi + 4i = 3 + 7i Reorder the terms: -5 + 4i + 3iy + 4x = 3 + 7i Solving -5 + 4i + 3iy + 4x = 3 + 7i Solving for variable 'i'. Move all terms containing i to the left, all other terms to the right. Add '-7i' to each side of the equation. -5 + 4i + 3iy + -7i + 4x = 3 + 7i + -7i Reorder the terms: -5 + 4i + -7i + 3iy + 4x = 3 + 7i + -7i Combine like terms: 4i + -7i = -3i -5 + -3i + 3iy + 4x = 3 + 7i + -7i Combine like terms: 7i + -7i = 0 -5 + -3i + 3iy + 4x = 3 + 0 -5 + -3i + 3iy + 4x = 3 Add '5' to each side of the equation. -5 + -3i + 3iy + 5 + 4x = 3 + 5 Reorder the terms: -5 + 5 + -3i + 3iy + 4x = 3 + 5 Combine like terms: -5 + 5 = 0 0 + -3i + 3iy + 4x = 3 + 5 -3i + 3iy + 4x = 3 + 5 Combine like terms: 3 + 5 = 8 -3i + 3iy + 4x = 8 Add '-4x' to each side of the equation. -3i + 3iy + 4x + -4x = 8 + -4x Combine like terms: 4x + -4x = 0 -3i + 3iy + 0 = 8 + -4x -3i + 3iy = 8 + -4x Reorder the terms: -8 + -3i + 3iy + 4x = 8 + -4x + -8 + 4x Reorder the terms: -8 + -3i + 3iy + 4x = 8 + -8 + -4x + 4x Combine like terms: 8 + -8 = 0 -8 + -3i + 3iy + 4x = 0 + -4x + 4x -8 + -3i + 3iy + 4x = -4x + 4x Combine like terms: -4x + 4x = 0 -8 + -3i + 3iy + 4x = 0 The solution to this equation could not be determined.
| 2(c-3)=c+1 | | b+1=3b | | Ln(x)=0.480036 | | lnx=0.480036 | | 2x+3y=365 | | 2xg=15-3xg | | -13x^2+54x-60=0 | | 8x-18+x+18=90 | | -10x^2-3x+9=0 | | (x-3)*3=9 | | .8x=1.2 | | 12x-8x=162-43x | | 9x-66+x=94 | | 4+7x-4=5-2x+8x | | 2*x=15-3*x | | 4x^5+x-0.05=0 | | 9x^2+79=-18 | | 7x-6x-40=24 | | -23x^2+162x-180=0 | | 14=4x-18 | | 9000000+2000000x=5000000 | | 3x+14=7x-18 | | 4x^5+x-0.1=0 | | 2=v-5 | | 9000000x=500000 | | (4+z)(4z+2)=0 | | 4x+13+7x-9-2x=8x+24-6x+7-2x | | -12y=3x-6 | | -107+2x+10x=49 | | 9x^2-40x+39=0 | | 4y+5=5y-4 | | 7+49x=28x+13 |